EFFECT OF INFLATION ON THE FINANCIAL REPORTS PRESENTATION : CONSTANT RATE ANALYSIS METHOD - Hatta, Atika Jauharia (Accounting, 2010)
One information used by investor and others in making their decision is financial report. Management may communicate information about it plans or projections, but financial statement and most financial reporting are historical. To make it useful they should obtained some qualification such as relevant and reliable. An alternative to overcome this weakness by using general price level accounting methods.